Biophilic workspaces: a comparative study of visual attributes in government indoor office environments in Putrajaya, Malaysia - Zulkifli, Nabilah Huda (Malaysia Institute of Planners, 2024)
The paper examines the visual features of biophilic design patterns in indoor workspaces in government office buildings in Putrajaya. It aims to highlight and identify the biophilic elements in these workspaces. The perceived perception of biophilic design elements is recorded based on inventory lists using the author’s expertise—the comfort and health of building occupants, mainly indoors, need to be considered. Visual benefits from interacting with nature, directly and indirectly, are abundant, including improving mood, thus contributing to enhanced focus and concentration. Based on the observation conducted on the indoor workspaces in the government offices in Putrajaya, Malaysia, the prevalent elements identified are the usage of natural lighting and diffused light entering from windows, especially in the cellular offices, which indirectly provides an external view outside the office. The presence of natural elements, such as potted plants and flowers, pictures of nature, botanical elements at the door, building panels, and pillars, can be seen. Biophilic design in indoor working spaces must be encouraged to cater to office users’ physical and mental wellbeing, thus improving their performance at work.